2016
DOI: 10.1002/ajpa.22904
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Selection and the differences between the sexes inMandrills (Mandrillus sphinx)

Abstract: Sexual selection has become a major focus in evolutionary and behavioral ecology. It is also a popular research topic in primatology. I use studies of mandrills (Mandrillus sphinx), a classic example of extravagant armaments and ornaments in animals, to exemplify how a long-term, multidisciplinary approach that integrates field observations with laboratory methods can contribute to on-going theoretical debates in the field of sexual selection. I begin with a brief summary of the main concepts of sexual selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 330 publications
(504 reference statements)
1
34
0
Order By: Relevance
“…Furthermore, the small sample size and observation time per individual reduced the power of the analyses and limit our capacity to interpret and generalise our findings. The captive setting of the study group and our focus on females also limit our capacity to generalise the obtained results to wild groups; however, mandrills are very difficult to follow in the wild [63] and captive studies provide a rare opportunity to investigate their social behaviour.…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, the small sample size and observation time per individual reduced the power of the analyses and limit our capacity to interpret and generalise our findings. The captive setting of the study group and our focus on females also limit our capacity to generalise the obtained results to wild groups; however, mandrills are very difficult to follow in the wild [63] and captive studies provide a rare opportunity to investigate their social behaviour.…”
Section: Plos Onementioning
confidence: 99%
“…There is also substantial evidence that conspecifics can detect differences in these odors, and such odors may elicit behavioral or physiological changes in the odor recipient (Drea, ). More importantly, odor has been linked to variables (i.e., rank) important for mate choice in mandrills (Setchell, ), and are used in direct intra‐sexual competition through stink‐fights in ring‐tailed lemurs (Jolly, ) and reproductive suppression in some callitrichines (Ziegler, ). As a first step to identify potential chemosignals in a strictly socially monogamous pair‐living platyrrhine, we investigate the chemical components of glandular secretions in owl monkeys ( Aotus spp.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have found evidence of changes in sexual behaviors with age in male nonhuman primates, but there is limited evidence of a decrease in fertility (reviewed in 22 ). The ability to study reproductive senescence in free-ranging primates is limited by the confounding factor that many older males lose their high-ranking status prior to a decrease in their reproductive success 5,23,24 . For example, male baboons experience a decline in reproductive output as they age, but this decline coincides with a loss in dominance rank 5 .…”
mentioning
confidence: 99%